Endothelial cell dynamics post-Descemet’s stripping endothelial keratoplasty and their correlation with preoperative counts in corneal endothelial disorders: An observational study - Surya Prakash Shukla; Shweta Singh; Arun Sharma; Sanjiv Kumar Gupta (Journal of Clinical Ophthalmology and Research)
Aim: The aim of this study is to observe changes in endothelial cell count post-Descemet's stripping endothelial keratoplasty (DSEK) and analyze the correlation between pre- and postDSEK endothelial cell counts to see if a higher donor cell count improves graft longevity. Settings and Design: A prospective cross-sectional observational study was performed at a Medical University from August 2020 to July 2021. Materials and Methods: This study was conducted among 19 DSEK patients. Preoperative and postoperative endothelial cell density (ECD) was measured using clinical specular microscopy (NIDEK CEM 530). Data analysis was done using SPSS version 23.0. Statistical Analysis: Mean ± standard deviation (SD) was assessed using an independent t-test, and a paired t-test was used to compare the mean groups. Pearson correlation analysis was done to reveal a correlation between preoperative and postoperative cell count. Results: Out of the 19 patients, 13 had completed 6-month follow-up data. The mean preoperative endothelial cell count was 3031.9 cells/mm2 (SD ± 174.9), while the 6-month postoperative cell count was 1822 cells/mm2 (SD ± 145.1). There was a significant reduction in endothelial cell count (P < 0.05), with a mean loss of 1209.9 cells/mm2 (SD ± 130.1). Pearson correlation analysis depicted a nonsignificant, weak positive correlation (r = 0.065, P = 0.832) between preoperative and postoperative counts, indicating that the initial donor count may be a reliable predictor of postoperative outcomes. Conclusion: DSEK significantly reduces endothelial cell count 6 months postoperatively. Preoperative donor cell count does not significantly predict postoperative cell count.